Enterprises of the Fruit and Vegetable Cluster in Uzbekistan and Issues of Improving the Management System of Their Activities (Eurasian Journal of Research, Development and Innovation, 2022)
One of the most pressing issues today is to ensure an uninterrupted supply of food to the population of Uzbekistan and economic growth through the export of fruits and vegetables to world markets. This article describes the significance of the adopted legal documents to improve the management system in the activities of the country's fruit and vegetable cluster enterprises, as well as the development of the industry, and the results of ongoing work in this area